The Wnt/β-Catenin/LEF1 Pathway Promotes Cell Proliferation at Least in Part Through Direct Upregulation of miR-17-92 Cluster - Mu, Fang; Huang, Jiaxin; Xing, Tianyu; Jing, Yang; Cui, Tingting; Guo, Yaqi; Yan, Xiaohong; Li, Hui; Wang, Ning (Frontiers in Genetics, 2019)
The miR-17-92 cluster is involved in animal development and homeostasis, and its dysregulation leads to human diseases such as cancer. In the present study, we investigated the functional link between miR-17-92 cluster and Wnt/β-catenin signaling pathway in ICP2 and DF1 cells. We demonstrated that ectopic expression of either LEF1 or β-catenin increased the promoter activity of the miR-17-92 cluster host gene (MIR17HG) and combined ectopic expression of LEF1 and β-catenin further enhanced the promoter activity; while knockdown of either LEF1 or β-catenin reduced the MIR17HG promoter activity. Both LEF1 and β-catenin could directly bind to the MIR17HG promoter. Furthermore, we demonstrated that low doses of lithium chloride (LiCl), an activator of Wnt/β-catenin signaling pathway, increased MIR17HG promoter activity and the endogenous expression of the miR-17-92 cluster, while high doses of LiCl had the opposite effects. Treatment with XAV-939, an inactivator of the Wnt/β-catenin pathway, reduced the endogenous expression of miR-17-92 cluster. Finally, we found that low doses of LiCl promoted the proliferation of ICP2 and DF1 cells, while high doses of LiCl inhibited the proliferation of ICP2 and DF1 cells. Taken together, our results reveal that MIR17HG is a target of LEF1 and the Wnt/β-catenin pathway and suggest that the miR-17-92 cluster may, at least in part, mediate the proliferation-promoting effect of the Wnt/β-catenin pathway in cell proliferation.